(untitled) - Saleh, Bahaa E. A (New York, 1991)
Content this Chapter 19: The field of nonlinear optics comprises many fascinating phenomena. Linearity or nonlinearity is a property of the medium through which light travels, rather than a property of the light itself. Nonlinear behavior is not exhibited when light travels in free space. Light interacts with light via the medium. The presence of an optical field modifies the properties of the medium which, in turn, modify another optical field or even the original field itself
Quang học phi tuyến
Keywords: Photonics,Quang tử.